Level of Promotion, Service and Store Atmosphere on Purchase Decisions in Franchise Business (Alfamart) in Rantau Selatan District - Mika Indah Sari Hutauruk; Marlina Siregar; Pitriyani Pitriyani (Budapest International Research and Critics University, 2022)
Promotion is a step by the company in communicating with potential buyers. This type of research is quantitative, the place of this research is a franchise (Alfamart) in Rantau Selatan District. Data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The population in this study were all consumers who shopped at the franchise (Alfamart) in Rantau Selatan District. The number of indicators in this study is 20 indicators, so a minimum of 20 x 5 or 100 samples is needed.then the sample size in this study was 100 people.The analysis used is multiple linear regression. The results of the regression analysis obtained the t-count value of 2.927 > t table 1.6608. This means that the promotion level variable (X1) has a positive effect on the purchasing decision variable (Y). Then the significant value is 0.004 <0.05, which means the promotion level variable (X1) has a significant effect on the purchasing decision variable (Y). Based on the results of the regression analysis, the t-count value was 4.604 > t table 1.6608. This means that the service variable (X2) has a positive effect on the purchasing decision variable (Y). Then the significant value is 0.000 <0.05, which means the service variable (X2) has a significant effect on the purchasing decision variable (Y). Furthermore, the results of the regression analysis obtained the t-count value of 3.338> t table 1, 6608 this means that the store atmosphere variable (X3) has a positive effect on the purchasing decision variable (Y). Then the significant value is 0.001 <0.05, which means the store atmosphere variable (X3) has a significant effect on the purchasing decision variable (Y). Fcount value of 43.378> Ftable 2.70 with a significance value of 0.000 <0.05. From these results, it can be concludedpromotion level (X1), service(X2) and store atmosphere (X3) simultaneously has a positive and significant effect on purchasing decisions (Y). The value of R Square from the analysis of the coefficient of determination of 0.575 means that work productivity can be explained by the variablepromotion level (X1), service(X2) and store atmosphere (X3) of 57.5%, while the remaining 42.5% can be explained by other variables not examined in this study.